Performance evaluation and optimization of a fluidized three-dimensional electrode reactor combining pre-exposed granular activated carbon as a moving particle electrode for greywater treatment - Jung, Kyung-Won; Hwang, Min-Jin; Park, Dae-Seon; Ahn, Kyu-Hong (ELSEVIER SCIENCE BV, 2015)
This study deals with the application of a fluidized three-dimensional electrode reactor (F-TDER) system combining granular activated carbon (GAC) as a moving particle electrode and an electric field for greywater treatment by electrocoagulation. In order to eliminate the adsorption capacity of GAC, pre-exposed GAC (20 cycles) to greywater was employed. Through a series batch test, the four main key parameters as independent variables and each experimental range were determined (applied current, GAC dosage, initial pH, and reaction time). Statistical optimization of the F-TDER system was subsequently carried out by the response surface methodology with a Box-Behnken design to describe interactive effects of determined independent variables on the maximization of COD removal efficiency. From an analysis of variance, it was found that a quadratic polynomial model fitted with the actual data well (R-2 = 0.9709). The response surface analysis showed that GAC dosage, initial pH, and reaction time were more influential factors than applied current, and they had either slightly interdependent or significantly interactive effects on COD removal efficiency. The optimum conditions found were applied current of 354.3 mA, GAC dosage of 47.1 g/L, initial pH of 5.4, and reaction time of 55 min which resulted in 98.56 +/- 0.14% of COD removal efficiency. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: RESPONSE-SURFACE METHODOLOGY; GREY WATER-TREATMENT; WASTE-WATER; BED REACTOR; ELECTROCOAGULATION; REMOVAL; DEGRADATION; INDUSTRY; DESIGN; SLUDGE